Neuroprotective and antioxidant effects of ghrelin in an experimental glaucoma model - Can, Nagehan; Catak, Onur; Turgut, Burak; Demir, Tamer; Ilhan, Nevin; Kuloglu, Tuncay; Ozercan, Ibrahim Hanifi (Dove Medical Press Ltd, 2015)
Damage to retinal ganglion cells due to elevation of intraocular pressure (IOP) is responsible for vision loss in glaucoma. Given that loss of these cells is irreversible, neuroprotection is crucial in the treatment of glaucoma. In this study, we investigated the possible antioxidant and neuroprotective effects of ghrelin on the retina in an experimental glaucoma model. Twenty-one Sprague-Dawley rats were randomly assigned to three groups comprising seven rats each. The rats in the control group were not operated on and did not receive any treatment. In all rats in the other groups, IOP was increased by cauterization of the limbal veins. After creation of the IOP increase, saline 1 mL/kg or ghrelin 40 mu g/kg was administered intraperitoneally every day for 14 days in the vehicle control group and ghrelin groups, respectively. On day 14 of the study, the eyes were enucleated. Levels of malondialdehyde (MDA), nitric oxide (NO), and nitric oxide synthase-2 (NOS2) in anterior chamber fluid were measured. The retinas were subjected to immunohistochemistry staining for glial fibrillary acidic protein (GFAP), S-100, and vimentin expression. Mean levels of MDA, NO, and NOS2 in the aqueous humor were higher in the vehicle control group than in the control group (P<0.05). Mean levels of MDA, NO, and NOS2 in the ghrelin group did not show a significant increase compared with levels in the control group (P>0.05). Retinal TUNEL and immunohistochemistry staining in the vehicle control group showed an increase in apoptosis and expression of GFAP, S-100, and vimentin compared with the control group (P<0.05). In the ghrelin group, apoptosis and expression of GFAP, S-100, and vimentin was significantly lower than in the vehicle control group (P<0.05). This study suggests that ghrelin has antioxidant and neuroprotective effects on the retina in an experimental glaucoma model.
Keywords: experimental glaucoma; ganglion cells; ghrelin; neuroprotective; antioxidant